Polar Weather Satellite Receiver - Shamsudin, Norshariza (Universiti Sains Malaysia, 2006)
Polar weather satellite receiver is one of the important parts in the satellite communication system. The objective of this project is to display the weather’s image that this receiver received. The weather’s image can be seen in the computer. This satellite receiver scans continuously in never ending strip until the image complete. If the receiver had problems, then the signal sent could not be accepted. The satellite receiver combines 3 circuits to produce a complete system. The combinations of the circuits are the mixer circuit, oscillator circuit and also the superheterodyne FM receiver based on the specification given. But, there are a few problems occurred while this project had been carried out. Chips that are used in this project could not be found in the softwares such as Orcad and Altium, so the circuits designed could not be simulated. Because of this problems, the results from the output of the spectrum analyzer could not be differentiate with the simulation results. Besides that, the chips that had been booked arrived quite late so it affect the way this project is carried out. Another problem is that I had to switch to another circuit during the last minute because there are some chips that are booked arrived late and are not applicable. There are also components that are difficult to obtain. Lastly, the output for every circuit are observed and analysed to fulfill the given specifications.